A 'pivot' that never existed: America's Asian strategy under Obama and Trump. Issue 1 (2nd January 2019) - Kolmaš, Michal; Kolmašová, Šárka
Abstract: This article argues that Donald Trump's Asian strategy hardly marks a radical transformation from Barack Obama's 'pivot to Asia'. This is because the 'pivot to Asia' never really existed. Although Obama was successful in building legitimacy for the strategy through international norms, he failed to translate his lofty rhetoric into practice. Much of his original pivot components (building a constructive relationship with China, coordinating with Asian allies and multilateralism in the Association of South East Asian Nations and the Trans-Pacific Partnership) has either failed or did not live up to expectations. Donald Trump was adamant that the Asian pivot was a bad strategy and that he would not follow it. But although he completely discarded Obama's legitimization of the rebalance (as Trump speaks pragmatically and does not care about international norms), in actuality he has followed many of Obama's policies, and even improved on some of them. That being said, Trump's 'pivot actions' appear to be erratic, pragmatic short-term actions rather than a meticulously planned long-term strategy similar to Obama's rebalance (which did not materialize). Thus, while Obama failed to transform the pivot into an effective strategy, neither is Trump's effectiveness backed by a coherent Asian strategy.